A Content Analysis of Sports Summer Camp Curriculum for Elementary School Students by the Perspective of Multiple Intelligence Theory - Muchamad Arif Al Ardha; Chung Bing Yang; Wei Jhe Lin; Nurhasan Nurhasan; Setiyo Hartoto; Nanik Indahwati; Dwi Cahyo Kartiko; Heryanto Nur Muhammad; Fifukha Dwi Khory; Kolektus Oky Ristanto; Ainun Zulfikar Rizki (Studies in Philosophy of Science and Education, 2022)
Sedentary behavior and obesity are becoming international concerns. Children spent less time in physical activity and sports due to several reasons. Changing children’s behavior should involve a holistic approach. Furthermore, multiple intelligence could contribute to promoting active children's behavior. This study aimed to evaluate the content of the sports summer camp curriculum which was developed by multiple intelligence theory. Moreover, the effect on children's behavior was observed in the implementation of the curriculum. This research was conducted by a qualitative-quantitative combination research design (mixed method). There were 82 elementary school students (age 9.70 ± 1.18 years old) who participated as a research sample with the approval of their parents. As a result, there were eight intelligence profiles that were implemented into this curriculum. The intelligence was bodily-kinesthetic, linguistic, logical-mathematical, musical, visual-spatial, interpersonal, intrapersonal, and naturalist. Furthermore, based on their multiple intelligence profile, bodily-kinesthetic performed excellently in every activity. In addition, there is no significant difference in students’ involvement among multiple intelligence groups during the summer camp (Sig. >0.05). In conclusion, each intelligence was involved in the activity. Furthermore, each multiple intelligence group could involve in every activity.